Sol-gel synthesis and photocatalytic activity of biomimetic calcium manganese oxide catalysts. Issue 1 (October 2020) - Setyarini, W; Nurhayati,; Dewi, N; Anggraini, R; Siregar, S S; Amiruddin, E; Awaluddin, A
Abstract: The water contaminations by dye residues are increasingly becoming serious concerns worldwide due to dye toxicity and persistent characteristics. Manganese oxide-based catalysts having similar structures with manganese compounds found in nature (biomimetic) have been considered as a very promising and effective photocatalyst for the degradation of organic pollutions in wastewater. This paper focuses on the synthesis of calcium manganese oxide catalysts from the octahedral layered birnessite-type manganese oxide and calcium carbonate via sol-gel method with citric acid as the complexing agent. The as-synthesized oxide was then tested as a photocatalyst for the degradation of methylene blue (MB) dye. The calcium manganese oxides prepared by the two different mole ratios of CaCO3/MnO2 resulted in the similar crystallinity and crystal phases but difference in the crystal sizes. The photocatalytic activities of the prepared calcium manganese oxides for the degradation of methylene blue are compared to that of the calcium manganese oxide prepared from tunnel cryptomelane-type manganese oxide. Both the calcium manganese oxides prepared from the different manganese oxide phases show the remarkable performance for the photocatalytic degradation of methylene blue after 10 minutes of reaction times. The birnessite-prepared calcium manganese oxide displays slightly higher photocatalytic performance than cryptomelane-prepared calcium manganese oxide.